2008
DOI: 10.1186/1472-6807-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Docking of molecules identified in bioactive medicinal plants extracts into the p50 NF-kappaB transcription factor: correlation with inhibition of NF-kappaB/DNA interactions and inhibitory effects on IL-8 gene expression

Abstract: BackgroundThe transcription factor NF-kappaB is a very interesting target molecule for the design on anti-tumor, anti-inflammatory and pro-apoptotic drugs. However, the application of the widely-used molecular docking computational method for the virtual screening of chemical libraries on NF-kappaB is not yet reported in literature. Docking studies on a dataset of 27 molecules from extracts of two different medicinal plants to NF-kappaB-p50 were performed with the purpose of developing a docking protocol fit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 21 publications
8
46
0
Order By: Relevance
“…Despite the fact that other ligand-based similarity searches for the selection of compounds for the docking run were possible, the ligand library preparation involved a forward filter based on substructure searching was used, by deriving 2D chemical information from a biologically active molecule previously discovered by us. [10] This method was used in order to potentially increase compound potency as well as the VS enrichment factor. In total 1484 structures, including tautomers, were sampled in the library to be screened with docking simulations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that other ligand-based similarity searches for the selection of compounds for the docking run were possible, the ligand library preparation involved a forward filter based on substructure searching was used, by deriving 2D chemical information from a biologically active molecule previously discovered by us. [10] This method was used in order to potentially increase compound potency as well as the VS enrichment factor. In total 1484 structures, including tautomers, were sampled in the library to be screened with docking simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, NF-kB as a target for this application could present potential limitations: 1) no 3D structure of NFkB-small ligand complexes are available, 2) the DNA binding site has a large contact surface area and is accessible to water, 3) some side chains of the interaction area assume different rotameric states depending on DNA conformation, and 4) most ligands show rather small binding constants (micromolar range). Nevertheless, in a previously published study [10] in which a set of 27 compounds from bioactive plant extracts were docked into p50 NF-kB, an inhibitor of NF-kB p50-DNA interaction and correlated IL-8 gene expression was identified.…”
Section: Introductionmentioning
confidence: 99%
“…Other amino acids involved in the formation of H-bond include Leu for octadecanoic Several plant-derived bioactives have been reported as potential inhibitors of NF-κB by interacting with the enzyme directly (Nam, 2006). Using in silico and in vitro techniques Piccagli et al (2008) reported similar binding of bioactives from medicinal plants against NF-κB and concluded that the docking result is predictive of biochemical activity.…”
Section: Resultsmentioning
confidence: 89%
“…10 The best ligand docking gold score value was 55.03 with lowest binding energy of -6.03 (kcal/mol) and formed H-bonding with six amino acid residues (E 282, P283, V244, K221, H 181, I196) of p65 subunit of NF-κB ( Figure 5 and Table 1). In a mini review survey by Patrick,18 showed the list of amino acid residues involved in interactions between IκBα and p50/ p65.The amino acids in p65subunit, Y20, E 22,E49, H181, K 221, S 238, 10 studied the amino acids of p50/p65 heterodimer involved in DNA binding and revealed that 13 p50 residues (C59, K144, Y57, Q274, Q306, R305, K145, K272,S63, G65, G66, N136, K77) and twelve p65 amino acids (C38, K122, Y36, K123, Q220, Q247,R246, K221, A 43, S42, S45, K56) made several contacts in DNA backbone.…”
Section: Molecular Docking Of Procyanidin B 2 Against Nf-κbmentioning
confidence: 99%
“…9 In response to a variety of stimuli including physical and chemical stresses, cytokines, reactive oxygen intermediates and ultraviolet light, the latent cytoplasmic NF-κB/IκBα complex is activated by the I-κB Kinase (IKK) complex. 10 IKK is formed by three distinct subunits: IKKα, IKKβ and IKKγ. The activation of IKK complex leads to the phosphorylation by IKKβ of which targets IκB for ubiquitination and degradation by the 26S proteasome.…”
Section: Introductionmentioning
confidence: 99%